A Simple, Analytically Solvable Chamberlinian Agglomeration Model - Michael Pflüger (Institute for the Study of Labor (IZA), 2001)
This paper presents a simple, analytically solvable Chamberlinian agglomeration model. As in the canonical core-periphery (CP) model, two agglomerative forces are at work. However, the present model exhibits a 'pitchfork bifurcation' rather than the 'tomahawk bifurcation' of the CP model.
Keywords: F12; F15; F22; R12; 330; Economic geography; agglomeration; human capital mobility; Regionale Konzentration; Kern-Peripherie-Beziehung; Außenwirtschaftstheorie; Neue ökonomische Geographie; Mark-up Pricing; Internationale Arbeitsmobilität; Humankapital; Dynamisches Gleichgewicht; Theorie